Geoweb 2.0 for Participatory Urban Design: Affordances and Critical Success Factors. (September 2014) - Pak, Burak; Verbeke, Johan
In this paper, we discuss the affordances of open-source Geoweb 2.0 platforms to support the participatory design of urban projects in real-world practices. We first introduce the two open-source platforms used in our study for testing purposes. Then, based on evidence from five different field studies we identify five affordances of these platforms: Conversations on alternative urban projects, citizen consultation, design empowerment, design studio learning and design research. We elaborate on these in detail and identify a key set of success factors for the facilitation of better practices in the future.